The Nigerian Mangrove and Wildlife Development - Abere, S.A.; Ekeke, B.A. (Mediterranean Journal of Social Sciences, 2011)
The Nigerian mangrove ecosystem is mostly fragmented deltaic formation located in the River Niger Delta.Occasionally what should have been continuous and uniform mangrove forest in the Delta Islands areinterrupted by beach Ridge Island forests sandwiched between the coastal beaches and the estuarinemangrove and island within the mangrove forests. The beach ridge forests typically contain lowland rainforestspecies. Some have large areas of high quality forests with high concentrations of biodiversity as in Andoniarea.